Total HLA Class I Antigen Loss with the Downregulation of Antigen-Processing Machinery Components in Two Newly Established Sarcomatoid Hepatocellular Carcinoma Cell Lines - Wei-Yi Lei; Shih-Chieh Hsiung; Shao-Hsuan Wen; Chin-Hsuan Hsieh; Chien-Lin Chen; Christopher Glenn Wallace; Chien-Chung Chang; Shuen-Kuei Liao (Journal of Immunology Research)
Limited information is currently available concerning HLA class I antigen abnormalities in sarcomatoid hepatocellular carcinoma (sHCC). Here, we have analyzed the growth characteristics and HLA class I antigen status of four sHCC cell lines (sHCC29, sHCC63, sHCC74, and SAR-HCV); the first three were newly established in this study. Among the four, sHCC29 showed the highest growth rate in vitro and tumorigenicity in NOD-SCID mice. Unlike sHCC74 and SAR-HCV, both sHCC29 and sHCC63 had no detectable surface HLA class I antigen expression, alongside undetected intracellular β2-microglobulin (β2m) and marked HLA class I heavy chain and selective antigen-processing machinery (APM) component downregulation. The loss of β2m in sHCC29 and sHCC63 was caused by a >49 kb deletion across the B2M locus, while their downregulation of APM components was transcriptional, reversible by IFN-γ only in several components. β2m was also undetected in the primary HCC lesions of the patients involved, indicating its in vivo relevance. We report for the first time HLA class I antigen loss with underlying B2M gene deficiency and APM defects in 50% (2 of 4) of the sHCC cell lines tested. These findings may have implications for a proper design of T cell immunotherapy for the treatment of sHCC patients.